Policy suggestion for Korean defense GRI - HWANG, Sooyoon (KDI School, 2016)
The purpose of this study is to review the transformation trend of other advanced nations’ defense GRIs cases and find some implications that can be applied to the Republic of Korea (“ROK”) defense Government Research Institutes (“GRIs”). In order to prepare for future warfare and military tension with military powers and North Korea, the ROK should secure its own core and strategic technology through efficient defense Research and Development (“R&D) policy. Through case study and comparison study between Korea and three advanced nations (France, the UK and Israel), this paper suggests 3 main implications. First of all, a special defense GRI which is in charge of core and strategic defense R&D is required. Secondly, the ROK defense industry should develop their own defense R&D capacity and lead practical R&D for weapon system projects. Government and GRI support are essential to strengthening Korean defense industries’ competitiveness. Thirdly, entire governance reform is required for ultimate change. To deal with the current ROK defense R&D issues and conduct consistent defense R&D procedure, some parts of three GRIs(DAPA, ADD and DTAQ) should be merged or relocated under MOD.
Thesis(Master) --KDI School:Master of Public Policy,2016